Linear Hedge Fund Index Replication – Revolutionizing Hedge Fund Industry or Introducing Poor-performing Alternatives for Hedge Funds? - Pajunen, Taru (My University, 2016)
Hedge funds have historically been important investments in diversified portfolios of wealthy individuals and institutional investors. However, recent economic environment and events including the financial crisis of 2008 have increased investors’ awareness of the restrictions related to hedge funds such as high fees, lock- up periods, illiquidity and lack of transparency. Roused by these problems some investors have begun to look for products yielding returns similar to hedge funds without their disadvantages. The goal of this thesis is to conduct and examine the linear hedge fund replication portfolios that aim to generate returns comparable to hedge funds with lower fees and increased transparency, functioning as potential components of alternative investment allocation. In this thesis, linear multivariate factor models are estimated to ten Credit Suisse Hedge Fund Indices from the Credit Suisse Asset Management LLC –database in order to examine risk exposures of these indices to common factors during time period from 2004 to 2015. Eight different factors, selected based on previous research and their ability to explain the hedge funds’ risk exposures are included in the model. The estimated beta coefficients from the risk exposure analysis are then used as portfolio weights for the eight factors in order to conduct monthly returns for the replication products. Both fixed-weight linear clones and 24-month rolling-window linear clones are conducted. The monthly clone returns for both fixed-weight and rolling-window clones are compared to their target Credit Suisse Hedge Fund Indices. Results suggest that for certain indices a significant fraction of their risk can be captured by common factors in the linear factor model. Although the performance of the linear clones can be inferior to their hedge fund index benchmarks, they still offer similar levels of diversification benefits as the target indices. Finally, neither the fixed-weight nor the 24-month rolling window linear clones do perform well enough to be considered as alternatives to hedge funds.
Keywords: Hedge fund replication; passive hedge fund replication; risk exposure analysis; linear factor model; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|